European evidence based consensus on the diagnosis and management of Crohn's disease: current management. (15th February 2006) - Travis, S P L; Stange, E F; Lémann, M; Öresland, T; Chowers, Y; Forbes, A; D'Haens, G; Kitis, G; Cortot, A; Prantera, C; Marteau, P; Colombel, J-F; et al.
Abstract : This second section of the European Crohn's and Colitis Organisation (ECCO) Consensus on the management of Crohn's disease concerns treatment of active disease, maintenance of medically induced remission, and surgery. The first section on definitions and diagnosis includes the aims and methods of the consensus, as well as sections on diagnosis, pathology, and classification of Crohn's disease. The third section on special situations in Crohn's disease includes postoperative recurrence, fistulating disease, paediatrics, pregnancy, psychosomatics, extraintestinal manifestations, and alternative therapy for Crohn's disease.